Strategy Of PT. Karya Sehati Utama (KSU) In Increasing Buying Interest Through Marketing Mix - Nur Rachman, Naba’il; Hartono, Arif (Cita konsultindo, 2025)
The internship activities carried out by the author aim to see how PT. Karya Sehati Utama, which operates in the property industry in Yogyakarta and its surroundings, can implement a good marketing mix strategy. PT. Karya Sehati Utama is one of the largest developers in Yogyakarta, which focuses on property development such as housing and villas. As a company in the property industry, PT. Karya Sehati Utama implements a 4P marketing mix strategy (product, price, place, promotion) to design and market projects that are in accordance with customer needs and market trends. To be able to find out the process, the author took observation data that was carried out directly and obtained 3 sources as a validity test. The method used by the author in compiling this internship report uses a qualitative method and uses triangulation testing. The analysis technique in this study consists of 3 activity flows that run simultaneously, namely: data reduction, data presentation and drawing conclusions. The results of this internship show that with the implementation of the marketing mix in the company, it has a significant influence on marketing activities so that the products offered can attract consumer buying interest.